Dynamic changes in betanin content during the growing season of table beet: their interplay with abiotic factors - D. V. Sokolova (Вавиловский журнал генетики и селекции)
The table beet, a widespread edible root crop known for its medicinal and antioxidant properties, early maturation, good shelf life, and high contents of bioactive compounds, vitamins and minerals, is used for the production of a natural red food dye. The relevance of this study is dictated by the lack of knowledge about the dynamic changes in the content of betanin during the growing season when developing table beet cultivars with a focus on pigment extraction. The article presents the results of a study of 29 red-colored table beet accessions from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). Dynamic changes in the content of the pigment during the growing season were observed on two beet accessions, cvs. ‘Russkaya odnosemyannaya’ and ‘Bordo odnosemyannaya’. Four pH versions of the buffer solution were tested, and the test results are presented. A buffer solution with pH 6.5 is recommended for research purposes. The amplitude of variability in the content of betanin in the peel (39.9–239.2 mg/100 g) and flesh (14.4–127.5 mg/100 g) of beets was determined. It was confirmed that the content of betanin in the peel exceeded that in the flesh in all samples. A positive relationship between these indicators was revealed (r = 0.74, p ≤ 0.05). It was found that betanin accumulation did not occur in beet roots during the growing season. The pigment showed considerable fluctuations associated with abiotic environmental factors. Correlation analysis showed a significant positive relationship between air temperature and betanin content in the root flesh (r = 0.32–0.31, p ≤ 0.05). A negative impact of environmental temperature on betanin content in the peel manifested itself on the third day (r = –0.34…–0.35, p ≤ 0.05). The negative response to precipitation was less expressed in cv. ‘Bordo odnosemyannaya’ due to the genotype’s more active metabolism and plasticity. Structural morphological features of the photosynthetic apparatus were described for the tested accessions, and their interrelations with the studied character were specified. Recommendations are given concerning the choice of a planting pattern and the timing of table beet harvesting for pigment extraction.